1963
DOI: 10.1111/j.1476-5381.1963.tb02021.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF PROSTAGLANDIN E1 ON RESPONSES OF SMOOTH MUSCLE TO CATECHOL AMINES, ANGIOTENSIN AND VASOPRESSIN

Abstract: Reduction of the pressor responses to adrenaline in the rabbit following administration of prostaglandin E1 has been confirmed. The effect is, however, nonspecific since noradrenaline, angiotensin and vasopressin are also antagonized. Analogous responses were observed in blood flow experiments on the cat hind limb but not on the rabbit isolated auricles or the rabbit isolated duodenum. Contractions of the cat nictitating membrane produced by sympathetic preganglionic stimulation or by adrenaline were not decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

1964
1964
1989
1989

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…Thus, the released prostaglandins act more by limiting the residual actions of the agonists (or the release of the transmitter) after the stimulus has been withdrawn. Holmes et al (1963) also found that prostaglandin E1 reduced the duration, but not the force of contraction of the cat nictitating membrane elicited by nerve stimulation. These results support the hypothesis that prostaglandin release attenuates the effects of nerve stimulation by a feed-back loop, but suggest that such a loop has a time constant measured in minutes rather than seconds.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the released prostaglandins act more by limiting the residual actions of the agonists (or the release of the transmitter) after the stimulus has been withdrawn. Holmes et al (1963) also found that prostaglandin E1 reduced the duration, but not the force of contraction of the cat nictitating membrane elicited by nerve stimulation. These results support the hypothesis that prostaglandin release attenuates the effects of nerve stimulation by a feed-back loop, but suggest that such a loop has a time constant measured in minutes rather than seconds.…”
Section: Discussionmentioning
confidence: 89%
“…Such a dose injected intravenously into anaesthetized cats would cause a substantial fall in blood pressure (Holmes, Horton & Main, 1963), and therefore the possibility cannot be excluded that part of the short-lived sedative effect seen on intravenous injection is secondary to this fall of blood pressure. The effects following intraventricular injection, however, cannot be explained in this way, since by the intraventricular route much smaller doses were effective than on intravenous injection, and the effects were not only sedation but also stupor and catatonia.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms are incompletely understood, though they appear to act through several systems. The natriuretic and vasodilator actions on the kidneys (McGiff, Crowshaw & Ifskovitz, 1974) and peripheral vasculature (Holmes, Horton & Main, 1963) are probably of greatest importance. In addition to these, there are also relevant actions at adrenal (Dazord, Morera, Bertrand & Saez, 1974) and uteroplacental sites (Speroff, 1975).…”
Section: Introductionmentioning
confidence: 99%